A new species of Osmia from Iran (Hymenoptera: Megachilidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2006)
A new species of Osmia, subgenus Helicosmia, is described and figured from a male and female collected near Karaj, Iran. Osmia (Helicosmia) mediana sp. n. can be superficially confused with O. (H.) indigotea Morawitz and in other respects O. (H.) adae Bingham. The new species is diagnosed and distinguished from other Helicosmia.
Keywords: entomologija; favna; Iran; kožokrilci